Novel insights from non-conserved microRNAs in plants - Qin, Zhengrui; Li, Chunlian; Mao, Long; Wu, Liang (Frontiers in Plant Science, 2014)
Plant microRNAs (miRNAs), a class of small non-coding regulatory RNAs, are canonically 20–24 nucleotides (nt) in length and bind to complementary target RNA sequences, guiding target attenuation via mRNA degradation or translation inhibition. Of the annotated miRNA families, evolutionarily conserved families have been well known to extensively regulate analogous targets and play critical roles in plant development and adaptation to adverse environments. By contrast, majority of these families that are merely present in a specific lineage or in a few closely related species have not been well functionally explored until recently. The fast-growing progresses being made in the actions of non-conserved miRNAs nowadays in diverse plant species may represent a highly promising research field in future. This review thereby summarizes the emerging advances in our understanding of the biogenesis, associated effectors, modes to targets, and biological functions of plant non-conserved miRNAs. In addition, it outlines the regulatory units recently discovered between conserved miRNAs and their alternative targets.